2022
DOI: 10.1590/0366-69132022683873309
|View full text |Cite
|
Sign up to set email alerts
|

A review on the production of porous ceramics using organic and inorganic industrial waste

Abstract: The use of industrial waste in compositions of ceramic masses has attracted great interest from the scientific community, as they can be considered abundant and diversified alternative sources of raw materials. At the same time, there is a growing interest in the development of porous ceramics due to their wide possibilities for use in various fields of engineering. In this sense, the present work aimed to provide a literature review on the use of industrial waste as alternative raw materials in the production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 102 publications
0
0
0
Order By: Relevance
“…Low thermal conductivity due to increased porosity was achieved by addition of organic waste in ceramics. [19] Three traditional charcoal cook stoves tested by Boafo showed that the cook stove insulated with a ceramic liner performed better in terms of thermal efficiency. [20] Material analysis by Schreiner showed that use of straw in clay mixture improves thermal efficiency.…”
Section: Improving Thermal Efficiency Using Organic Wastementioning
confidence: 99%
“…Low thermal conductivity due to increased porosity was achieved by addition of organic waste in ceramics. [19] Three traditional charcoal cook stoves tested by Boafo showed that the cook stove insulated with a ceramic liner performed better in terms of thermal efficiency. [20] Material analysis by Schreiner showed that use of straw in clay mixture improves thermal efficiency.…”
Section: Improving Thermal Efficiency Using Organic Wastementioning
confidence: 99%
“…Em contrapartida, materiais cerâmicos porosos apresentam vantagens, como elevado ponto de fusão e resistência à corrosão e ao desgaste. Crescentes avanços na tecnologia de processamento de materiais cerâmicos associados à demanda por materiais porosos se destacaram por suas amplas possibilidades de uso em vários campos da engenharia, desde tratamento de água até isolamento térmico e acústico e suporte catalítico (SILVA et al, 2022).…”
Section: Conformação De Materiais Cerâmicos Porososunclassified